ANALISIS EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN PAJAK HOTEL, PAJAK RESTORAN, DAN PAJAK REKLAME TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN TABALONG PROVINSI KALIMANTAN SELATAN - Fitri Rahmatika; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to determine the level of effectiveness and contribution of hotel tax, restaurant tax and advertisement tax to the Regional Original Income of Tabalong Regency, South Kalimantan Province. The data collection method used is the documentation method in which the data is taken from the Office of the Regional Tax and Retribution Management Agency, Tabalong Regency, South Kalimantan Province. The data analysis technique used in this research is descriptive statistical analysis, effectiveness analysis and contribution analysis. The results of the study stated that the effectiveness of the hotel tax, restaurant tax and advertisement tax from 2016-2020 fluctuated, namely the average hotel tax was 104.2965, the average restaurant tax was 109.382% and the advertising tax average was 65.454%. The highest effectiveness of the three highest 2016-2020 budget taxes is on the restaurant tax in the very effective category. Of the three taxes that contribute to PAD, the highest average is restaurant tax at 8.38%, hotel tax with an average contribution of 1.32% and the smallest contribution to advertising tax is 0.21%. Of the three taxes have not been said to contribute.Keywords: Effectiveness, revenue contribution, hotel tax, restaurant tax, advertisement tax, PAD